Biology and Population of Sergestid Shrimps (Acetes Spp.) (Decapoda: Sergestidae) From Klebang Besar, Malacca, Malaysia - Nurul Amin, Sanker Mohammad (2008)
Taxonomy, morphometric variation, population genetics, reproductive cycle, sex ratio, fecundity, feeding habits, seasonal abundance, growth, mortality, recruitment, yield-per-recruit and status of the stock of Acetes spp., locally known as ‘udang geragau’, from the coastal waters of Klebang Besar, Malacca, Peninsular Malaysia were examined during February 2005 to March 2007. Three species of sergestid shrimps viz A. indicus, A. japonicus and A. intermedius were identified from the study area. Among them, A. intermedius was recorded for the first time from Malaysia coast. All morphometric characters amongst the three species were significantly different (P < 0.05). The Random Amplified Polymorphic DNA (RAPD) marker was used to study the population genetic variation of A. japonicus collected along the west coast of Peninsular Malaysia. A total of 90 samples of Acetes japonicus, comprised of 30 (15 males and 15 females) from Kedah, 30 (15 males and 15 females) from Perak and 30 (15 male and 15 females) from Malacca were used. The percentages of polymorphic bands of the three geographic populations investigated were varied from 57.77% to 87.77%. Genetic distances between populations and cluster analysis from UPGMA grouped the populations into two major clusters. The Perak and Malacca populations were in one cluster, while the Kedah population was clustered by itself indicating it was genetically different. The genetic distance was the highest for the Kedah and the Malacca populations while the lowest was for the Perak and the Malacca populations which probably has a closed ancestral relationship and are from the same species. The sex ratio of A. indicus and A. japonicus in the coastal waters of Malacca was in favour of females in most months of the year. The analysis of the annual variation of gonadosomatic index (GSI) showed the continuously breeding of A. indicus and A. japonicus throughout the year. Size at first sexual maturity of female A. indicus was observed at 23 mm and that was > 17 mm of total length for female A. japonicus. There were no females with spent ovaries in the samples of both species. The estimated mean fecundity of A. indicus was 1666.28 (± 46.32) eggs. The mean monthly GSI for females A. indicus showed positive and significant (P < 0.05) correlation with conductivity (r = 0.67), salinity (r = 0.65) and TSS (r = 0.59)). No significant (P > 0.05) correlation was found between the mean monthly GSI and the remaining two variables (temperature and dissolved oxygen). According the Simple Resultant Index (%Rs), the stomach contents of A. indicus were comprised of plant matters (22.85%), fine sand and mud (16.19%), crustacean appendages (19.03%), debris (15.46%), unidentified fragments (10.56%), zooplankton (6.78%), phytoplankton (6.47%), algae (3.49%), shrimp nauplii (1.25%) and mollusc larvae (0.91%). Similarly, diet compositions of A. japonicus were made up of plant matters (31.82%), debris (20.06%), phytoplankton (18.45%), fine sand and mud (11.75%), appendages of decapods (6%), unidentified fragments (5.86%), algae (4.17%) and zooplankton (1.80%). These various compositions of food items proved that the two shrimps are bottom feeder omnivore. The average monthly catch per unit effort (CPUE) of the estuarine push net (EPN) was estimated at 2.50 (± 3.42) kg/fisherman/hr. The total catch comprised of three major categories those were Acetes shrimps (90%), followed by fish juveniles (9%) and other shrimps (1%). The annual percent composition of A. indicus, A. japonicas and A. intermedius were found to be 57%, 41% and 2%, respectively. The peak catch was observed in the month of October to December. There was no significant correlation (P > 0.05) between monthly catches and environmental parameters (temperature, dissolved oxygen, salinity, conductivity and total suspended solid). The length frequency distribution for A. indicus suggested that the population consisted of two dominant age group with mean values of 20.80 (± 0.07) mm and 29.85 (± 0.09) mm of the total length, respectively. And the population of A. japonicus consisted of maximum two age groups, with means of 15.18 (± 0.90) mm and 21.56 (± 1.03) mm of total length. The population of A. intermedius also consisted of maximum two age groups, with means of 19.18 (± 0.05) mm and 26.92 (± 0.06) mm of the total length. The positive allometric nature of growth for A. indicus was observed. However, isometric nature of growth was found in combined sexes of A. japonicus. The positive allometric nature of growth was also observed in female and both sexes of A. intermedius. There were significant difference between males and females size-frequency distribution of A. indicus (Kolmogorov-Smirnov test: dmax = 0.42, P < 0.05), A. japonicus (Kolmogorov-Smirnov test: dmax = 0.39, P < 0.05) and A. intermedius (Kolmogorov-Smirnov test: dmax = 0.40, P < 0.05). The growth, mortality, recruitment and relative yield per recruit of Acetes spp. were investigated based on monthly length-frequency data, using FiSAT software. Higher natural mortalities of male A. indicus and A. japonicus versus the fishing mortalities observed from the study indicated the unbalance position in the stock. Exploitation level (E) of female was higher than males in A. japonicus population. This study indicated two major recruitment events per year where two cohorts were produced per year for A. indicus and A. japonicus populations. The recruitment pattern of A. intermedius was continuous with one major cohort per year. Results from the analysis of the exploitation rate (E) based on the fishing mortality estimates, and from the relative yield-per-recruit (Y/R), indicate that the Acetes japonicus fishery is over exploited although A. indicus and A. intermedius fishery were slightly below the optimum level of exploitation. This implies that any further unrestrained increase in fishing effort might overshoot the level giving maximum sustainable yield, thus driving the stock down and leading to economic losses.